MPC-15 CLINICAL FEATURE OF NON-MIDLINE GLIOMA WITH H3F3A GENE MUTATION. (3rd December 2022) - Nakatogawa, Hirokazu; Kawaji, Hiroshi; Hayashi, Nobuhide; Fukai, Junya; Kijima, Noriyuki; Shofuda, Tomoko; Yoshioka, Ema; Kanematsu, Daisuke; Katsuma, Asako; Sumida, Miho; Inenaga, Chikanori; Mori, Kanji; et al.
Abstract: Introduction: Diffuse midline glioma (DMG), H3K27-altered, is a CNS WHO grade 4 glioma that usually occurs mainly in the brainstem region in children and also in the thalamus and spinal cord in older children and adults. On the other hand, glioma with histone H3 p. G34R/V mutations in the cerebral hemispheres are defined in a new classification of Diffuse hemispheric glioma, H3G34-mutant (DHG), in the WHO 2021 classification. However, there are some reports of H3K27-altered non-midline gliomas (NDMG) that are not located in the midline, but the differences between these hemispheric tumors with mutations in different regions of histone H3 are unknown. In this study, we report a comparative study of the clinical characteristics between two groups of glioma, H3K27-altered NDMGs and H3G34-mutant DHGs. Methods: Among 4128 brain tumor specimens collected in the Kansai Network for Molecular Diagnosis of Central Nervous System Tumors, 25 NDMG cases, excluding 93 cases defined as DMG, were included out of 118 cases with mutations in the H3F3A gene. Both 16 H3K27-altered NDMG cases and 9 H3G34-mutant DHG cases were examined for comparison of clinical characteristics. Results: There were no differences in gender, tumor location, or pathology between NDMG and DHG. The median age was 47.3 years in NDMG and 26.2 years in DHG, and NDMG was significantly older than DHG (p=0.003). The rate of MGMT promoter methylation is no significant difference between 4 cases (25%) in NDMG and 6 cases (66.7%) in DHG (p=0.087). The Kaplan-Meier survival curve showed no significant difference, with a median survival of 495 days for NDMG and 587 days for DHG (p=0.765). Discussion and Conclusion: We reported on gliomas with H3F3A mutations that occur in the cerebral hemispheres. We compared the clinical characteristics of NDMG with H3K27-altered and DHG with H3G34-mutant, which have similar tumor locations of occurrence.